2013
DOI: 10.1248/bpb.b13-00268
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Heat Exposure Impairs Nigrostriatal Dopaminergic Neurons in Mice

Abstract: Environmental heat stress is associated with physical stress responses, including changes in monoamines, protein expression, and neuronal circuits and damage to neurons in the brain. This study determined the effects of heat stress on the nigrostriatal dopaminergic system based on behavioral, histological, and neurochemical analyses. To evaluate behavioral changes after heat exposure, we subjected mice to the pole and open field tests. The data suggested that heat stress for 7 d significantly impaired movement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 27 publications
3
22
0
Order By: Relevance
“…In addition, other dopaminergic genes - DBH , TH , and ADCY1 - were also down-regulated by HS. This is consistent with the finding that heat stress reduces TH immunoreactivity in striatal dopamine neurons in mice and impairs nigrostriatal dopaminergic neurons and motor function [58].…”
Section: Resultssupporting
confidence: 92%
“…In addition, other dopaminergic genes - DBH , TH , and ADCY1 - were also down-regulated by HS. This is consistent with the finding that heat stress reduces TH immunoreactivity in striatal dopamine neurons in mice and impairs nigrostriatal dopaminergic neurons and motor function [58].…”
Section: Resultssupporting
confidence: 92%
“…To clearly elucidate the heat-cognition relationship, we examined the dependency on heat exposure time. Based on a previous report [6, 14], we chose the following experimental methods and conditions: humidity (60 ± 10 %), temperature (43 °C), exposure duration (15 min/day), subject number (n = 12), and memory test paradigms (Y-maze, novel object recognition task, and passive avoidance test). By conducting a longitudinal study, we clearly demonstrated that heat exposure per se had an inhibitory effect on cognition in mice.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies showed that heat stress can cause cell death in the brain [6, 35, 36, 50]. Activated glial cells in the brain produce neurotoxic factors that subsequently lead to neuronal death [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jia et al (2013) found that pretreatment with prostaglandin E1 and somatostatin alleviated ER stress by the induction of HSP70 (another member of the HSP70 family) and GRP78. Kim et al (2013) demonstrated that GRP78 gradually increased in the mouse substantia nigra with 28-day heat exposure. Recently, GRP78 expression was found to be related to disease occurrence.…”
Section: Introductionmentioning
confidence: 96%